Sustainable finance: A journey toward ESG and climate risk - Monica Billio; Michele Costola; Iva Hristova; Carmelo Latino; Loriana Pelizzon (Leibniz Institute for Financial Research SAFE, 2022)
The present paper proposes an overview of the existing literature covering several aspects related to environmental, social, and governance (ESG) factors. Specifically, we consider studies describing and evaluating ESG methodologies and those studying the impact of ESG on credit risk, debt and equity costs, or sovereign bonds. We further expand the topic of ESG research by including the strand of the literature focusing on the impact of climate change on financial stability, thus allowing us to also consider the most recent research on the impact of climate change on portfolio management.
Keywords: M14; G24; G11; 330; environmental; social; and governance factors (ESG); credit risk; debt cost; equity cost; sovereign bonds; portfolio management